PENGARUH SUBSTITUSI TEPUNG PISANG KEPOK TERHADAP KUALITAS COOKIES - Rangkuti, Nurhamidah; Yuliana, Yuliana; Holinesti, Rahmi (Journal of Home Economics and Tourism, 2015)
This study aimed to analyze the effect of substitution of banana flour kepokas much as 15%, 30% and 45% of the wheat flour used to the quality of brownishyellow color, uniform shape, form a neat, crescent-shaped, fragrant aroma ofbanana kepok, brittle texture, sweetness , and the banana flavor kepok. Theresearch is a pure experiment with completely randomized design method usingthree repetitions with 30 panelists. The results showed that the substitution ofbanana flour kepok effect on the quality of brownish yellow color, forms a neat,crescent shape, fragrant aroma of banana kepok, crumbly texture and taste ofbanana kepok that in general there is good value in treatment 45% (X3) than theother treatmentsKeywords: influence, banana flour substitution kepok, quality cookies